Enumerating the preventive youth health care workforce: Size, composition and regional variation in the Netherlands. Issue 12 (December 2015) - Jambroes, Marielle; Lamkaddem, Majda; Stronks, Karien; Essink-Bot, Marie-Louise
Highlights: This study examined the capacity of the youth health care workforce in the Netherlands. Workforce size was not in line with indicators of youth health needs. Our strategy, based on essential public health services, offers promising results to enumerate the public health workforce in general. The results indicate the need for integrated preventive youth health care workforce planning. Abstract: The progress in workforce planning in preventive youth health care (YHC) is hampered by a lack of data on the current workforce. This study aimed to enumerate the Dutch YHC workforce. To understand regional variations in workforce capacity we compared these with the workforce capacity and the number of children and indicators of YHC need per region. A national survey was conducted using online questionnaires based on WHO essential public health operations among all YHC workers. Respondents ( n  = 3220) were recruited through organisations involved in YHC (participation: 88%). The YHC workforce is multi-disciplinary, 62% had >10 years working experience within YHC and only small regional variations in composition existed. The number of children per YHC professional varied between regions (range 688–1007). All essential public health operations were provided and could be clustered in an operational or policy profile. The operational profile prevailed in all regions. Regional differences in the number of children per YHC professional were unrelated to the indicators of YHC need. The essential public health operations provided by the YHC workforce and the regional variations in children per YHC professional were not in line with indicators of YHC needs, indicating room for improvement of YHC workforce planning. The methodology applied in this study is probably relevant for use in other countries.